Ion cyclotron resonance heating with shifted separatrix. (9th March 2021) - Kolesnichenko, Ya.I.; Patten, H.; Lutsenko, V.V.; Graves, J.P.; Rudenko, T.S.; Contributors, JET
Abstract: Ion cyclotron resonance heating, which we refer to as ICRH-SS, with the quasilinear (QL) separatrix (i.e., the separatrix in the space of QL routes of ion acceleration) located in the region of passing particles is studied. The aim of ICRH-SS is to minimize the fraction of trapped particles (particles with small longitudinal velocities) in the population of fast ions. The basic idea of ICRH-SS—shifting the separatrix to the region of passing particles—was advanced in the paper (Kolesnichenko et al 2017 Nuclear Fusion 57 066004). In this work, new features of ICRH-SS are revealed. The 3D QL routes of the particle acceleration and effects of Coulomb collisions are studied. A QL equation for distribution function of neutral beam injection (NBI) ions, which is convenient for analysis, is derived. Conditions for QL flux prevailing over collisional flux caused by pitch scattering are obtained. Numerical simulations using the SCENIC package are carried out for a JET plasma with NBI ions that are accelerated by RF field in the core region. A JET pulse designed as a demonstration of the so called 'three ions' scheme, which also complies with the criteria of ICRH-SS scheme, was selected. The numerical results show that in the considered example most accelerated ions have larger longitudinal velocities and fast particle orbits are passing during ICRH-SS, whereas, 'conventional' ICRH (defined as ICRH with the separatrix in the region of trapped particles) produces accelerated ions with banana orbits. Numerical results also show an increase in fast ion generation and core plasma heating performance for ICRH-SS as compared to the conventional ICRH.